Corporate social responsibility in a local subsidiary: internal and external stakeholders' power. Issue 3 (16th September 2019) - Marques, Pilar; Bernardo, Merce; Presas, Pilar; Simon, Alexandra
Abstract : Purpose: Using a theoretical and empirical focus on the power stakeholders exert, the purpose of this paper is to provide a better understanding of the factors that influence the subsidiaries of multinationals' participation in corporate social responsibility (CSR) under the pressures (expectations and demands) their complex system of internal and external stakeholders' places upon them. Design/methodology/approach: Using an in-depth case study, the relationship a local subsidiary in the food and beverage industry has with its stakeholders as regards CSR is analyzed. Findings: The findings illustrate three main aspects: how the local company is affected by and how it affects its stakeholders (an example of the multidirectionality of power and influence); the direct and indirect practices that are adopted to address challenges; and the importance of the role the local subsidiary plays as an implementer and diffuser of its parent organization's responsible practices across the industry value chain. Originality/value: To the best of authors' knowledge, the focus is on analyzing the power stakeholders have in the context of multinational companies that has not been applied before, and the outcome of using this approach is that the authors have uncovered gaps in the literature for future research.